This preview shows page 1. Sign up to view the full content.
Unformatted text preview: former is much easier to evaluate: 1 4 3 = 1 2 3 = 1 8 1 4 3 = 1 64 = 1 8 3. (3 points) Simplify the rational expression x x +23 2 x1 . x x + 23 2 x1 = x (2 x1) ( x + 2)(2 x1)3( x + 2) ( x + 2)(2 x1) = x (2 x1)3( x + 2) ( x + 2)(2 x1) = 2 x 24 x6 2 x 2 + 3 x2 4. (3 points) Expand the polynomial 2 x 3( x 2x )( x + 2) . 2 x 3( x 2x )( x + 2) = 2 x 3( x 3 + 2 x 2x 22 x ) = 2 x 3x 32 x 2 + x 2 + 2 x = x 3x 2 + 2 x 5. (3 points) Using any method you like, solve the equation x 23 x = 6 . We start by writing the entire quadratic on a single side of the equation, as x 23 x6 = 0. Then, using the quadratic formula: x =(3) p (3) 24 1(6) 2 = 3 33 2 Page 1 of 1 Friday, January 14, 2011...
View Full
Document
 Spring '08
 Staff
 Calculus, Inequalities

Click to edit the document details